Effect of Tamsulosin on Biomarkers after Kidney Stones Lithotripsy - Iman A. Ismael (Institute of Medico-legal Publications Pvt Ltd, 2022)
The disease of kidney stones is one of the urinary system’s oldest and most common issues. Children with kidney stones have also become more popular, In recent years. Kidney stones are also very painful, and in some people, they can continue to occur. Kidney stone attacks result in over 2 million visits to health care facilities . People tend to get stones in the middle of life. During midlife, family and work commitments are at their height, which makes kidney stones costly. The diagnosis, treatment and prevention of kidney stones and the time away from work due to stones cost approximately 5.3 billion a year. To understand the effect renal some biomarkers in patients with kidney stones, before and after Lithotripsy and to evaluate the effect of Tamsulosin on these biomarkers in patients. Forty patients and twenty healthy persons were participate in this case-control study, Bl.urea, level of ALP, Level of KIM1, and level of Na c were investigate in serum with kidney stones patients and control healthy persons. The results were shown significant elevation in the levels of KIM-1, and serum urea were decreased significantly (p value <0.05) while the levels of ALP and serum sodium show an improvement when compared to patients who were not used tamsulosin but it’s results were statistically not significant. the results were given an evidence for the crucial role of some biomarker in serum in patients with kidney stones, also the effects of using tamsulosin for 14 days in patients with kidney stones who underwent lithotripsy compared with those patients who were not used tamsulosin.